Comprehensive non-invasive and invasive functional assessment of anomalous coronary arteries with anatomical high-risk features. (14th October 2021) - Bigler, M R; Spano, G; Boscolo Berto, M; Ueki, Y; Otsuka, T; Huber, A T; Raeber, L; Graeni, C
Abstract: Background: Anomalous aortic origin of a coronary artery (AAOCA) is a rare congenital disease associated with an increased risk of myocardial ischemia. In AAOCA, the occurrence of ischemia is based on the extent of a fixed and a dynamic component, each attributed to different anatomical high-risk features (i.e., acute take-off angle, slit-like ostium, proximal narrowing, elliptic vessel shape and intramural course). Coronary computed tomography angiography (CCTA) is the primary non-invasive imaging method to depict the presence and quantitatively assess anatomical high-risk features while invasive physiologic evaluation under maximal dobutamine-volume challenge is the gold standard to unravel the hemodynamic relevance of AAOCA. Methods: We included all consecutive AAOCA patients with anatomical high-risk features from our prospective, open-label registry. The objective is to quantify anatomical high-risk features in the CCTA and to measure hemodynamic relevance using invasive fractional flow reserve with maximal dobutamine-volume challenge (gradually increasing dose of dobutamine max. 40 μg/kg per body weight/min, max. 3000 mL ringer lactate and max. 1mg atropine). Pathological invasive FFR was defined as FFR Dobutamine<0.80. Additionally, CCTA-data were processed to assess computational fluid dynamics (CT FFR) and intravascular ultrasound (IVUS) was used to determine minimal lumen area (MLA) during baseline and maximal stress conditions. Results: A total of 11 patients were included between 05/19 and 11/2020. Mean age was 59±13 years (range: 40–79), 10 patients showed a right-AAOCA and one patient showed a single right coronary artery. All patients had either one (i.e., in 1 patient) or more than one anatomical-high risk features (i.e., in 10 patients). Mean invasive FFR Dobutamine was 0.88±0.07 with n=2 (18%) being pathological. Mean non-invasive CT FFR was 0.89±0.04 (FFR<0.80; n=0), mean invasive FFR Adenosine was 0.92±0.06 (FFR<0.80; n=1; 9%). There was a significant decrease in IVUS MLA between rest (7.93±2.79mm 2 ) and under dobutamine-volume challenge (6.57±3.20mm 2, p=0.008). Mean percentage of MLA reduction was 19±18%. Conclusion: Our preliminary results provide evidence that relevant myocardial ischemia seems to be often absent in a middle-aged population with AAOCA and anatomical high-risk features. However, in a minority of cases hemodynamic relevance could be depicted, especially when stressing with dobutamine-volume challenge. The presence of a dynamic component in AAOCA is represented by the reduced minimal lumen area under stress conditions. Comprehensive diagnostic evaluation should be performed to prevent unnecessary guideline recommended open-heart surgery in a middle-aged population with AAOCA. FUNDunding Acknowledgement: Type of funding sources: None.